Non-nuclear estrogen receptor alpha activation in endothelium reduces cardiac ischemia-reperfusion injury in mice. (June 2017) - Menazza, Sara; Sun, Junhui; Appachi, Swathi; Chambliss, Ken L.; Kim, Sung Hoon; Aponte, Angel; Khan, Sohaib; Katzenellenbogen, John A.; Katzenellenbogen, Benita S.; Shaul, Philip W.; Murphy, Elizabeth
Abstract: Steroid hormone receptors including estrogen receptors (ER) classically function as ligand-regulated transcription factors. However, estrogens also elicit cellular effects through binding to extra-nuclear ER (ERα, ERβ, and G protein-coupled ER or GPER) that are coupled to kinases. How extra-nuclear ER actions impact cardiac ischemia-reperfusion (I/R) injury is unknown. We treated ovariectomized wild-type female mice with estradiol or an estrogen-dendrimer conjugate (EDC), which selectively activates extra-nuclear ER, or vehicle interventions for two weeks. I/R injury was then evaluated in isolated Langendorff perfused hearts. Two weeks of treatment with estradiol significantly decreased infarct size and improved post-ischemic contractile function. Similarly, EDC treatment significantly decreased infarct size and increased post-ischemic functional recovery compared to vehicle-treated hearts. EDC also caused an increase in myocardial protein S-nitrosylation, consistent with previous studies showing a role for this post-translational modification in cardioprotection. In further support of a role for S-nitrosylation, inhibition of nitric oxide synthase, but not soluble guanylyl cyclase blocked the EDC mediated protection. The administration of ICI182, 780, which is an agonist of G-protein coupled estrogen receptor (GPER) and an antagonist of ERα and ERβ, did not result in protection; however, ICI182, 780 significantly blocked EDC-mediated cardioprotection, indicating participation of ERα and/or ERβ. In studies determining the specific ER subtype and cellular target involved, EDC decreased infarct size and improved functional recovery in mice lacking ERα in cardiomyocytes. In contrast, protection was lost in mice deficient in endothelial cell ERα. Thus, extra-nuclear ERα activation in endothelium reduces cardiac I/R injury in mice, and this likely entails increased protein S-nitrosylation. Since EDC does not stimulate uterine growth, in the clinical setting EDC-like compounds may provide myocardial protection without undesired uterotrophic and cancer-promoting effects. Highlights: Non-nuclear estrogen receptor activation with EDC reduces ischemia-reperfusion injury. EDC mediated protection does not depend on cardiac estrogen receptor-alpha. EDC mediated protection requires endothelial estrogen receptor-alpha. EDC mediated protection increases S-nitrosylation of cardiac proteins.